2021
DOI: 10.3389/fcell.2021.745637
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-4 Is a Soluble Dermal Inflammatory Signal That Selectively Promotes Fibroblast Migration and Keratinocyte Proliferation for Skin Regeneration and Wound Healing

Abstract: Thrombospondin-4 (THBS4) is a non-structural extracellular matrix molecule associated with tissue regeneration and a variety of pathological processes characterized by increased cell proliferation and migration. However, the mechanisms of how THBS4 regulates cell behavior as well as the pathways contributing to its effects have remained largely unexplored. In the present study we investigated the role of THBS4 in skin regeneration both in vitro and in vivo. We found that THBS4 expression was upregulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Additionally, osteopontin knockout mice have impaired wound closure (Wang et al, 2017). Thbs4 (Thrombospondin 4, an ECM protein; ear: log2(CAST/MRL) = -1.24, FDR = 6.55 x 10 -38 ; dorsal: log2(CAST/MRL) = -0.23, FDR = 0.048) has previously been shown to promote wound healing by stimulating fibroblast migration and keratinocyte proliferation (Klaas et al, 2021) and is reported to promote angiogenesis and reduce fibrosis (Stenina-Adognravi and Plow, 2019), with mouse Thbs4 knockout associated with damaging cardiac inflammation and fibrosis (Frolova et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, osteopontin knockout mice have impaired wound closure (Wang et al, 2017). Thbs4 (Thrombospondin 4, an ECM protein; ear: log2(CAST/MRL) = -1.24, FDR = 6.55 x 10 -38 ; dorsal: log2(CAST/MRL) = -0.23, FDR = 0.048) has previously been shown to promote wound healing by stimulating fibroblast migration and keratinocyte proliferation (Klaas et al, 2021) and is reported to promote angiogenesis and reduce fibrosis (Stenina-Adognravi and Plow, 2019), with mouse Thbs4 knockout associated with damaging cardiac inflammation and fibrosis (Frolova et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of cell types and response modulators, such as growth factors, cytokines, matrix metalloproteinases, cellular receptors, and extracellular matrix components are involved in initiation and proper progression of wound healing. As demonstrated recently by us and others [ 2 , 3 ], coordinated signals from the ECM and from the mesenchymal and infiltrated cells instigate and promote the stepwise progression of wound healing towards re-epithelialization and scar maturation.…”
Section: Introductionmentioning
confidence: 88%
“…LC-MS/MS protein analysis of this liquid demonstrated a significant increase in haptoglobin and thrombospondin-4 in the TGM-treated wounds (Fig. S3b, c), which are known to influence macrophage differentiation and epithelial cell migration, respectively (41)(42)(43)(44).…”
Section: Topical Tgm Treatment Accelerated Wound Closurementioning
confidence: 98%